Political culture in Bangladesh : perspectives and analysis : selections from the journal of Bangladesh studies - Andaleeb, Dr. Syed Saad.; Bangladesh Development Initiative (Dhaka : Bangladesh Development Initiative : University Press, 2007)
Contributed articles on various aspects of history of Bangladesh serialized earlier in Journal of Bangladesh studies.
Includes bibliographical references and index.
Keywords: Bangladesh -- History